Sleep Disordered Breathing in Patient with Type 2 Diabetes Mellitus and its Association with Diabetic Retinopathy: Single Center Study - Sijapati, Milesh Jung; Pandey, Minalma; Karki, Poojyashree; Khadka, Nirupama (Nepalese Medical Journal, 2019)
Introduction: Sleep-disordered breathing comprises of obstructive sleep apnea, central sleep apnea, and periodic breathing. There is a link between obesity diabetes and sleep apnea with its association with retinopathy. Therefore this study was done to find out the association of sleep-disordered breathing in uncontrolled diabetes mellitus and association with retinopathy. Materials and Methods: This study was done from 2015 September to 2018 September in Sleep center, Nepal. Patients diagnosed with Type 2 diabetes mellitus were included. Diabetes mellitus was diagnosed as blood sugar fasting ≥ 126mg/dl, or blood sugar postprandial ≥200mg/dl and glycosylated hemoglobin above 6.5%. Obstructive sleep apnea risk was determined using the STOP-BANG questionnaire. Relationships between the risk of Obstructive sleep apnea and clinical variables along with its association with diabetic retinopathy were evaluated using bivariate analyses and covariate-adjusted logistic regression models. Results: A total of 150 diabetic patients were analyzed. Among them 30 (20.0%) patients had mild Obstructive sleep apnea, 14 (9.3%) patients had moderate Obstructive sleep apnea and 15 (10.0%) patients had severe sleep apnea. Among patients with diabetes mellitus on multivariate regression analysis Obstructive sleep apnea was associated with diabetes mellitus OR 2.05, 95% CI (1.69- 8.83) and diabetic retinopathy OR 1.20 (0.67-5.89). Conclusions: This study concludes that those individuals having diabetes may be suffering from obstructive sleep apnea and association with retinopathy these individuals can be considered for the screening of sleep-disordered breathing by polysomnography.